SIFAT-SIFAT GEOTEKNIK BAHAN TIMBUNAN INTI KEDAP AIR BENDUNGAN BATUTEGI - Didiek Djarwadi (Faculty of Engineering, Universitas Gadjah Mada, 2003)
Soil was already widely used as watertight materials in the embankment dam engineering, where as, the selection and treatment (compaction) will in/Iuenced the geotechnical properties.As a water tight material the soil used should be impermeable for controlling seepage and hwe efficient shear strength for controlling stability.The aim of this research was to analyze the soil laboratory test results of core embanlcrnentmaterials obtained during the soil investigation and the construction stages of the Batutegi dam,a 125 meter in height of earth-rockfill dam in Lampung, Indonesia. The research analyzed thegeotechnical parameters and the intercelations of the geotechnical parameters in order to indicate the geotechnical properties of the core embankment materials. The evaluation of the geotechnical parameters from the soil laboratory tests indicated that in term of density, permes-bility, swelling characteristic, compressibility as well as the strength, the core moterials used at Batutegi dam meets the requirement as watertight materials in the embankment dam engineering.Keywords: geotechnical properties, embankment dam, water tight materials.